HUBUNGAN POLA ASUH ORANG TUA TERHADAP TINGKAH LAKU SOSIAL REMAJA DI NAGARI SUNGAI JANIAH KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Idrawati, Idrawati; Kasih, Fitria; Yusnetti, Yusnetti (Bimbingan dan Konseling, 2013)
This research means to know about The Relationship between parent caring pattern with the adolescent social habit in area Sungai Janiah district Gunung Talang sub-province Solok. The kind of research that be used is descriptive correlation. Population in this research are all adolescents of area Sungai Janiah district Gunung Talang. Sample of population are taken by random sampling method which is from the counting, the amount of sample must be 51 people. The instrument in this research is enquette. That enquette concist of two kind of enquette, there are parent caring pattern enquette and adolescentâs social habit enquette. Then, these enquette is tested the validity and reliability. To analyze it, used the equation ofÂ product moment correlation coefisien karl pearson. The result of counting then is compared with product moment value r table and then doing t test which also be compared with t value table and last determinant coefisien counting of those two variable. The result of research show that there are a significant and strong relationship between The Relationship of parent caring pattern with the adolescent habit in area Sungai Janiah district Gunung Talang sub-province Solok, where rhitung about 0,73 >Â rtabel about 0,279 at df 50 with significant value 5%.